O modelo de regulação do programa nuclear brasileiro e suas implicações com os princípios da precaução e prevenção - Braga, Dimis da Costa (2014)
This paper proposes a critical analysis of the regulation of the nuclear power program in Brazil, in comparison with the principles of precaution and prevention, and suggests the need for public debate on the issue of energy, do that government and society to democratically define the optimal energy mix for the country. After discusses sustainable development correlated to citizenship in accordance with the Federal Constitution of Brazil of 1988, describes the history of nuclear energy in the world, and particularly in Brazil, analyzing the risk of damage that can cause to the environment and people. In order to understand the logic arising out from the nuclear model proposed in Brazil, indicates the evolution of the Brazilian experience and the impact of the deployment of nuclear energy project, from the agreement between Brazil and Germany in the 1970s. Finally, comments the duties of the Comissão Nacional de Energia Nuclear - CNEN and its contradictions in relation to sustainable development anchored on the principles of precaution and prevention as key elements Environmental Law.